Investigating the Credibility of Online Travel Reviews Adoption on Social Media in Trip Planning Intention: Scale Development & Validation of Modified IAM - Kaur, Jasveen; Kaur, Jobanjeet (Turizam, 2022)
This study aims to develop a scale and validate the modified Information Adoption Model (IAM) in the tourism context. Secondly, the impact of online review usefulness is determined by online review adoption while accessing the mediation role of travelers’ attitude toward online reviews between review usefulness and its adoption. Further, the credibility of travel review adoption on the behavioral intentions of travelers has been assessed. This paper adapts the modified IAM given by Abedi et al. (2019) to scale development and provide a comprehensive model in the tourism context. The study used 284 travelers who use online travel reviews from social media for their trip planning to evaluate the proposed model using Smart PLS software. The results show that online travel review usefulness significantly affects online travel review adoption by travelers. Secondly, the relationship between online review usefulness and adoption is fully mediated by the mediating variable (attitude towards online reviews). This empirical paper intends to overcome the research gap in social media based on travel review adoption by travelers for their trip planning, considering the behavioral intentions of the travelers. It validated a modified Information Adoption Model (IAM) by considering the recipients’ characteristics (attitude toward online reviews) and behavioral intentions (purchase intentions and forwarding of the information). Travelers evaluate online travel reviews through their use. As a result, travel marketers such as hoteliers, destination marketers and travel agency websites managers should set up mechanisms to assess tourists' concerns to avoid unfavorable social media reviews. Because an unfavorable traveler's experiences are more severe than a favorable one, companies should promptly react to customer concerns and make appropriate changes to enhance their services. These activities provide consumers with a feeling of security. This lessens the urge to propagate unfavorable information about travel service providers.